Optimalisasi literasi halal pelaku UMKM terhadap penggunaan jasa keuangan syariah di Kota Tebing Tinggi - Cynthiasari, Vina; Yafiz, Muhammad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Halal literacy of MSME actors has not been optimal in encouraging MSME actors to use Islamic financial services. In recent years, the halal industry through the food, finance, clothing, tourism, media and recreation, medicine and cosmetic sectors has experienced rapid development. This study aims to increase the halal literacy of MSME actors towards the use of Islamic financial services in the City of Tebing Tinggi. This research is a research (field research) using a field approach to produce descriptive data. The data comes from interviews and observations of MSME actors who are members of the IPEMI (Indonesian Muslim Entrepreneurs Association) in Tebing Tinggi City as primary data, as well as secondary data obtained from research locations, journals, books, documents, and records related to research. It can be said that the halal literacy of MSME actors still has the food sector, such as raw materials, production processes, and packaging. Although MSME actors have not been able to describe the halal relationship with Islamic financial services, indirectly MSME actors have the awareness to use or are interested in Islamic financial services.